Vertical stratification of bird community in Cikepuh Wildlife Reserve, West Java, Indonesia - ROLISKA VIRGO DINANTI; NURUL LAKSMI WINARNI; JATNA SUPRIATNA (Society for Indonesian Biodiversity, 2018)
Dinanti RV, Winarni NL, Supriatna J. 2018. Vertical stratification of bird community in Cikepuh Wildlife Reserve, West Java, Indonesia. Biodiversitas 19: 134-139. The complexity of heterogeneous strata can be used to determine the distribution of resources in bird communities. However, deforestation causes damage and may disturb the bird community in the forest. Cikepuh Wildlife Reserve in West Java, Indonesia is an example of degraded forest due to deforestation. Illegal logging in the area leads to approximately 7000 hectares of forest conversion into a plantation area. This study was conducted to test the hypothesis of the differences in the diversity of birds in each stratum of vegetation and the differences in the diversity of birds in forest and plantation. The study was conducted in March 2016. Point count method was used for bird surveys. The calculation of Shannon-Wiener diversity index showed that forest had a higher diversity of birds (H? = 3.09) than plantation (H? = 2.78). Based on the rank abundance graph, each vegetation stratum had a different type of curve. The middle canopy layer had the highest bird abundance while the emergent and understory layers had the lowest abundance.